(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
A field research was conducted for during 2016-2017 season, in the fields at Al-Mussaib of Babylon Governorate. Using a (RCBD) (split plot design) with three replicates to four varieties (IPA 99, Abu-Ghraib, Tamoz and Alfeteh). Objective of the study were for Genotypic, phenotypic alterations and coefficient of variability , broad sense heritability fraction and expected genetic advance also genotypic and phenotypic correlation for some traits of wheat, under two levels of organic fertilizer (10 and 15 ton/ ha-1). The results showed. Significant difference among varieties used in research and all most studied characters with the highest second of level 15 ton/ ha-1 of organic. The genotypic and phenotypic variance were more than environment variance for two levels to the all studied characters. Furthermore high estimates of broad sense heritability were observed for all characters and the highest value to up 98% (number of spikes and biological yield ) at the first Level, While (grain number and yield) under the second level. While values of expected genetic advance the high for all characters to up 66.6 and 61.99, under two levels, respectively. While genotypic and phenotypic coefficients of difference, the lowest in most of the traits under both levels. Yield and number of grain gave the high significant positive genotype correlation for spike at the first level, with number of spikes under the second level. Therefore, it can be concluded that selection program of wheat in study genetic parameters under different levels of the organic fertilizers are best for development of plants were observed on the highest values are found in most traits.